Evaluation of suburethral transobturator sling procedure on urinary incontinence and quality-of-life - Coelho, Maria L.; Pinho, António de; Castro, Fabiana; Freixo, Marília; Melo, Anabela; Torres, Sílvia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Urinary incontinence has an estimated incidence of 25-50% in the adult female population. It has a profound physical and psychosocial impact, compromising women’s quality-of-life (QoL). The suburethral sling is currently considered the surgical treatment of choice for stress urinary incontinence (SUI). The present study aimed to evaluate the impact of urinary incontinence on women’s QoL before and after transobturator suburethral sling surgery, as well as the effectiveness of surgical treatment. Methods: A prospective longitudinal, observational and analytical study was performed between June and December 2021. The study population included 64 women with urinary incontinence, to whom the King's Health Questionnaire (KHQ) was applied, before and after surgery. Results: Of the 64 women included in the study, 59.4% (n=38) had SUI and 40.6% (n=26) had mixed urinary incontinence (MUI). There was an improvement in the global KHQ score in 96.9% (n=62) of subjects, with a statistically and clinically significant impact on QoL (p<0.001). Patients with MUI had higher preoperative KHQ global scores, reflecting a more substantial impact on their QoL. Surprisingly, postoperative improvement in QoL was equally significant, both clinically and statistically (p<0.001), with no differences when comparing to isolated sui patients (p>0.05). Conclusions: QoL assessment questionnaires help to quantify individual impact of urinary incontinence and identify which patients benefited most from treatment. This study not only enhances our understanding of the true impact of urinary incontinence on QoL, but also emphasizes the effectiveness and importance of this minimally invasive surgery in improving the QoL of patients with SUI as well as MUI.